2015
DOI: 10.1620/tjem.236.311
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fibroblast Growth Factor 10 Is Correlated with Poor Prognosis in Gastric Adenocarcinoma

Abstract: Fibroblast growth factor receptor 2 (FGFR2) has been proved to be a significant prognostic factor and a potential therapeutic target in several types of cancer, including gastric cancer. FGFR2 consists two isoforms: FGFR2-IIIb and FGFR2-IIIc, which can be stimulated by different ligands and trigger different downstream signaling pathways. As a specific ligand to FGFR2-IIIb, fibroblast growth factor 10 (FGF10) is expressed in the gastric mesenchyme cell and is involved in stomach development and morphogenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…At the genetic level, amplification of FGF genes may lead to their overproduction in GC, specifically, FGF10 amplification has been reported in 3% of GC and in 5.7% of gastric adenocarcinomas [82,83]. FGF10 is correlated to GC cell invasion and has been suggested as a prognostic biomarker and potential drug target in gastric adenocarcinoma [84]. In our recent study, we explored the FGF mRNA profiling in 10 GC cell lines by microarray analysis, where FGF18 showed the highest expression among all the FGF members.…”
Section: Deregulation Of the Fgf-fgfr Signaling In Gastric Carcinomentioning
confidence: 99%
“…At the genetic level, amplification of FGF genes may lead to their overproduction in GC, specifically, FGF10 amplification has been reported in 3% of GC and in 5.7% of gastric adenocarcinomas [82,83]. FGF10 is correlated to GC cell invasion and has been suggested as a prognostic biomarker and potential drug target in gastric adenocarcinoma [84]. In our recent study, we explored the FGF mRNA profiling in 10 GC cell lines by microarray analysis, where FGF18 showed the highest expression among all the FGF members.…”
Section: Deregulation Of the Fgf-fgfr Signaling In Gastric Carcinomentioning
confidence: 99%
“…In a cohort of 961 gastric cancers from the United Kingdom, Korea and China, FGFR2 amplification was detected in 4.2–7.4% of cases and was associated with lymph node metastasis and poor overall survival ( Su et al, 2014 ). FGF10 amplification has also been detected in 3% of gastric cancers ( Ooi et al, 2015 ) and immunohistochemical analysis of 178 gastric adenocarcinoma samples revealed that FGF10 levels are correlated with poor prognosis ( Sun et al, 2015 ). Interrogation of most recent cBioPortal data suggests this could be an underestimate, with FGF10 amplifications reported in 5.7% of stomach adenocarcinoma cases ( Cerami et al, 2012 ; Gao et al, 2013 ).…”
Section: Fgf10 In Stomach Cancermentioning
confidence: 99%
“…More recently, chromosomal translocation and duplication events at the loci of the Fgf10 and Fgfr2 genes have been associated with neurological disorders such as developmental delay and autism ( Casey et al, 2012 ; Wentz et al, 2014 ). The role of single nucleotide polymorphisms and de novo point mutations causing oncogenic expression of Fgf10 and Fgfr2 are also becoming clearer, particularly in pancreatic, gastric, and breast cancers ( Jang et al, 2001 ; Theodorou et al, 2004 ; Nomura et al, 2008 ; Reintjes et al, 2013 ; Su et al, 2014 ; Sun et al, 2015 ; Ghoussaini et al, 2016 ; Coci et al, 2017 ). (D) FGF10-dependent activation of FGFR intracellular tyrosine residues (Y; insert), adaptor proteins (gray), protein kinases (red), and transcription factors (blue).…”
Section: Introductionmentioning
confidence: 99%
“…Fgf10 knockout (KO) mice die at birth with defects in multiple organ development, including the limb, lung, kidney, salivary gland and adipose tissue ( Ohuchi et al, 2000 ). Fgf10 gene mutations have been associated with diseases, such as aplasia of lacrimal and salivary glands (ALSG) ( Entesarian et al, 2007 ) and lacrimo-auriculo-dento-digital (LADD) syndrome ( Rohmann et al, 2006 ); chronic obstructive pulmonary disease ( Klar et al, 2011 ) and certain cancer types, including breast ( Theodorou et al, 2004 ; Ghoussaini et al, 2016 ), pancreatic ( Nomura et al, 2008 ), and gastric ( Sun et al, 2015 ) cancers (Figure 1C ).…”
Section: Introductionmentioning
confidence: 99%